Evaluation of the Effectiveness of Cutting Scalpel Blades After Use and Leaning by Different Methods - Bruno de Oliveira Sampaio; Lívia Maria Andrade de Freitas; Nilton Cesar Nogueira dos Santos; Francisco Xavier Paranhos Coêlho Simões; Ana Carolina Del Sarto Azevedo Maia; Ricardo Alves de Souza; Ana Carolina Dias Viana de Andrade; Matheus Melo Pithon (Portal de Periódicos da Marinha do Brasil, 2022)
When performing incisions during oral and maxillofacial surgical procedures, the surgeon requires a blade that ensures precise cuts which reduce unnecessary tissue injuries. After searching the literature, we realized that there is a lack of studies that assesses scalpel blades for dental use. Herein, this study aims to assess the cutting power of new scalpel blades after cleaning with different methods. Sixty sterile scalpel blades were divided into seven groups: I) new blade; II) the second insertion; III) blade cleaned with gauze; IV) blade cleaned with gauze and saline; V) blade cleaned with saline; VI) blade cleaned with cotton, and VII) blade cleaned with cotton and saline. A universal testing machine (Osvaldo Filizola, São Paulo, Brazil) was used for the insertion and measurement of the shear strength. The results revealed that cleaning the blade with gauze and saline was the method that had the greatest loss of the cutting capability. The reinsertion of the scalpel blade without any type of cleaning or the cleaning of the blade with cotton and saline were the methods that obtained the best result, which did not compromise the mechanical properties of the tested material. This study concludes that cleaning methods affect the cutting power of scalpel blades.